Unlocking the power of Phyllanthus niruri - nature’s hidden gem - Vittal, Ramya; Kumari, Ch. Aruna; Priya, P. Bindu; Venugopal, U.; Madhavi, M. (Chronicle of Bioresource Management, 2023)
In the world of herbal remedies and natural medicine, few plants have captured the imagination of researchers and wellness enthusiasts quite like Phyllanthus niruri. Known by a variety of common names, including ‘stonebreaker’, ‘chanca piedra’, and ‘gale of the wind’, this unassuming herb has a rich history of use in traditional medicine across the globe. However, in recent years, it has gained significant attention for its potential health benefits and therapeutic properties. It boasts a nutritional profile rich in protein, carbohydrates, vitamins and minerals. The plant has a significant presence in Ayurveda and traditional Chinese medicine, primarily for its beneficial effects on kidney health, including kidney stone prevention and the promotion of their natural passage. Its medicinal potential extends to antiviral and antioxidant effects, combating viral infections, neutralizing free radicals and offering various other health benefits. Incorporating P. niruri into one’s wellness routine can be achieved through dietary supplements, herbal teas, tinctures or traditional recipes. P. niruri represents a valuable botanical resource with diverse health benefits, warranting careful consideration for its optimal utilization in holistic well-being approaches.